Privileged Scaffolds in Drug Discovery against Human Epidermal Growth Factor Receptor 2 for Cancer Treatment - Peerzada, Mudasir N.; Hamdy, Rania; Rizvi, Masood Ahmad; Verma, Saurabh (Current Pharmaceutical Design, 2023)
HER2 is the membrane receptor tyrosine kinase showing overexpression in several human malignancies, particularly breast cancer. HER2 overexpression causes the activation of Ras- MAPK and PI3K/Akt/ NF-ΚB cellular signal transduction pathways that lead to cancer development and progression. HER2 is, therefore, presumed as one of the key targets for the development of tumor-specific therapies. Several preclinical have been developed that function by inhibiting the HER2 tyrosine kinase activity through the prevention of the dimerization process. Most HER2 inhibitors act as ATP competitors and prevent the process of phosphorylation, and abort the cell cycle progression and proliferation. In this review, the clinical drug candidates and potent pre-clinical newly developed molecules are described, and the core chemical scaffolds typically responsible for anti-HER2 activity are deciphered. In addition, the monoclonal antibodies that are either used in monotherapy or in combination therapy against HER2-positive cancer are briefly described. The identified key moieties in this study could result in the discovery of more effective HER2-targeted anticancer drug molecules and circumvent the development of resistance by HER2-specific chemotherapeutics in the future.
Keywords: breast cancer